الأنظمة السياسية والأنماط الانتخابية-مقاربة مفاهيمية - بوروبي, عبد اللطيف (revue mofakir, 2018)
الملخص : إن الانتخاب هو سلوك قائم على التحول من نمط إلى نمط مستهدف،فهو وسيلة من الوسائل المشروعة للوصول إلى السلطة،يفهم في ظل تعريف، ونشأة، وخصائص وتجزئة للأهداف . يقوم على أشكال عدة مختلفة المستويات من العلاقات التفاعلية،كمستوى أول من التحليل بين المواطن والوصول إلى السلطة، وبين السلطة والأحزاب كمستوى ثاني، وبين المواطن والأحزاب كمستوى ثالث، وبين المواطن وطبيعة النظام السياسي القائم كمستوى رابع، ومن ثم فيه عدة جوانب سياسية، واجتماعية، وثقافية، واقتصادية، وأمنية تحدد تلك العلاقات . إن العامل المحدد في هذه التفاعلات، طبيعة النظام السياسي القائم والذي يحدد لنا طبيعة الأنماط الانتخابية، فإذا كان النظام السياسي ديمقراطي تأتي العملية الانتخابية واضحة،وتعبر عن رأي الشعب والعكس إذا كان النظام السياسي مغلق فتكون هناك تجاوزات وتعسف، وانتهاك للحقوق . نحتاج إذن إلى عدة مقاربات وصفية متعددة الاختصاصات لتحديد تلك الجوانب،وكل مقاربة لها أساس نظري حيث تبرز الحاجة إلى تحديدها من خلال صياغة إطار مفاهيمي للدراسة .( مقاربة مفاهيمية ) ،والذي يعتبر المدخل النظري الأقرب إلى الفهم، فتركيزنا يكون على العلاقة بين النظام السياسي والأنماط الانتخابية .   Summary The election is a behavior which is based on move from one method to a target one. It is then one of the legitim means to reach authority which is understood in the light of its definition, charactereristics and objectives. It stand in different levels of dynamics relationships. The first level of analysis is between the citizen and the authority, the second level ,however, is between the authority and the political parties. the third level between citizen and the political parties, the last one, the fourth is between the citizen and the standing political system. Since then, different political, social, cultural and security sides determine these relations. The main factor that determines these interactions is the nature of the standing political system which determine the nature of the election methods. in that ,if is the political system is democratic ,the election will reflect the people’s choice and free will. whereas ,when the political system is no democratic one there will so many acts such as abuses. We need then ,then, various descriptive approaches to determine the side, in each approach has a theoretical basis that needs to determined though the structure of a conceptual frame for the study. The conceptual approach represents the near theoretical entrance to the understanding where the focus will be on the relationship between the political system and the methods of election.